Palladium/N-heterocyclic carbene catalysed regio and diastereoselective reaction of ketones with allyl reagents via inner-sphere mechanism - Da-Chang Bai (Nature Portfolio, 2016)
Palladium catalyzed allylic substitution reactions typically proceed via an outer sphere mechanism, yielding predominately linear products. Here, the authors report an inner sphere process for the allylic substitution of ketone enolates, giving branched products with up to three contiguous stereocentres.